(untitled) (Global Journal of Human-Social Science, 2021)
This paper reviewed the matter of balance and trade-off between domestic debt and public debt. The study sought to underpin the general consensus on the issue of debt and how economic activities were impacted by the various forms of public debt. The paper gives an overview of different countries experience with regards to debt sourcing. Various authors express various views with regards to this question that do not necessarily bring about points of convergence in ideologies. The general point of agreement of specialists who have looked into this subject matter is established at the use of the debt acquired. If debt is acquired to facilitate development projects then there is no doubt that such debt will resultantly bring about economic growth and economic development. On the other hand there are some governments that do borrow for to finance recurrent expenditure however much that this increases consumption within the economy, the desired growth and development is hardly achieved. Worse still some of the funds acquired as a result of debt in some nations are squandered and pocketed by few individuals and this is very significant in the retrogressive states of many countries with weak systems that provide no serious check mechanisms as well as accountability and ownership of responsibility.